Kinetic and thermodynamic analysis of pyrolysis of oily cold rolling mill sludge of steel industry under non-isothermal conditions. Issue 4 (21st December 2022) - Wang, Hailu; Liu, Enhui; Zhao, Rongxuan; Ji, Aimin; Yao, Xin; Guan, Jinghua; Wu, Xuda
ABSTRACT: The pyrolysis is an effective technology for energy and resource recovery from oily cold rolling mill sludge (OCRMS) considered as hazardous waste. This study focuses on the pyrolysis behavior of OCRMS by thermogravimetric analysis (TGA). The kinetic and thermodynamic characteristics were obtained through different methods (Kissinger-Akahira-Sunose (KAS), Ozawa-Wall-Flynn (OWF), and Starink) under different heating rates (10 K/min, 15 K/min, and 20 K/min). And the reaction mechanism was investigated by integral master plots method. The average activation energy simulated with three methods was 65.68 kJ/mol, and the pre-exponential factor was between 265.6 to 871 s −1 within 0.2 to 0.9. Following change of conversion and heating rate the geometric and reaction order mechanisms played a leading role in turn. With the increase of heating rate, the change of enthalpy, Gibbs free energy, and entropy ranged from 60.39 to 59.99 kJ/mol, from 213.53 to 225.37 kJ/mol, and from −0.2407 to −0.2420 J/(mol·k), respectively. Pre-exponential factor indicates a relatively simple reaction process. The small difference of enthalpy change and average activation energy was helpful for generation of pyrolysis products. The change of Gibbs free energy change and entropy implied that the higher the energy consumption and promote the pyrolysis reaction, respectively.